Formulation and Stability of Exfoliating Liquid Soap Nanoemulsion from Lerak Extract (Sapindus rarak DC) and Coconut Dregs Waste - Istiqamah Harnama (CV. Syntax Corporation Indonesia, 2024)
The use of natural-based skincare products is increasing along with public awareness of the importance of choosing safe and environmentally friendly ingredients. This study aims to develop a nanoemulsion-based exfoliating liquid soap from lerak (Sapindus rarak DC) extract and coconut pulp. Considering the environmental challenges due to the use of plastic-based products, this study adopts an eco-friendly approach by using natural raw materials. The Ultrasonic-Assisted Extraction (UAE) method was applied to extract active compounds from lerak fruit, followed by the preparation of nanoemulsions using a high-pressure homogenizer. Results showed that the resulting nanoemulsion had good stability, with small droplet size and viscosity suitable for cosmetic products. Organoleptic tests showed that the final product was safe and non-irritating to the skin. The developed exfoliating liquid soap product shows potential as an environmentally friendly alternative to synthetic surfactant-based products. This research contributes to the development of sustainable cosmetic products that utilize local resources, as well as raising awareness of the use of natural ingredients in the beauty industry.